Prediksi Harga Saham Menggunakan Metode Extreme Learning Machine (ELM) (Studi Kasus: Saham PT Bank Rakyat Indonesia) - Yunita Dwi Lestari; Edy Santoso; Achmad Ridok (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Shares are a sign of ownership or membership of an entity or individual. The profit from the purchase of shares is derived from the acquisition of dividends and capital gains. The existence of stock trading in the secondary market, making the ups and downs of the share price so that there is a capital gain. A person who becomes a stock investor and takes advantage by selling shares he owns when the share price is higher than his previous purchase price is referred to as a trader. Due to fluctuations in the stock price, a trader needs analysis before making a stock purchase in order to avoid the risk of losses. In order to avoid losses of traders in the stock market, a stock price prediction system was created using the Extreme Learning Machine (ELM) method. After the prediction test with ELM obtained the most optimal parameters to make stock predictions, namely by using the number of data inputs 3, the number of hidden nodes 5, the type of activation function is binary sigmoid, and the ratio of training data and test data by 90% : 10% so that the average value of MAPE is obtained by 1.59722%.